Konflikt und Bewältigung Die Zerstörung der Grabeskirche zu Jerusalem im Jahre 1009 - Pratsch, Thomas (Millennium-Studien / Millennium Studies, 2011)
On September 28, 1009, Caliph al-Hakim had the Church of the Holy Sepulchre in Jerusalem destroyed. How did it come to this? What did it mean for contemporaries? Why were Jews persecuted as a result? Did it interrupt the stream of pilgrims to Jerusalem? What do we know about al-Hakim's personality? How was the crisis mastered? How was the church rebuilt? These are the questions considered in an interdisciplinary discourse by scholars of Arabic, Byzantine, Jewish, medieval and Nordic studies, as well as art historians and experts on the Christian East.